We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
154
4
avatar

3x+2y= -1

x−2y=5

 Sep 20, 2018
 #1
avatar+17990 
+2

Add the two equations together to get:

4x = 4       so x = 1     can you get the rest from this?

 Sep 21, 2018
edited by ElectricPavlov  Sep 21, 2018
 #2
avatar
+1

Thank you. No i am still unsure of how to carry out the rest of the problem. 

Guest Sep 21, 2018
 #3
avatar+17990 
+1

Substitute   x = 1   in to any of the equations ....then you can find 'y'....

ElectricPavlov  Sep 21, 2018
 #4
avatar+4084 
+1

3x+2y=-1, x=2y=5, adding both cancels out y, so we are left with: 4x=-1+5, 4x=4, x=1.

Plugging the value of x in the second equation to solve y, we have 1-2y=5, -2y=4, y=-2.

Check for the first equation: 3(1)+2(-2)=3-4=-1.

smileysmiley

 Sep 21, 2018

13 Online Users

avatar